1998
DOI: 10.1007/bf02884961
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial stress moderates the relationship of cancer history with natural killer cell activity

Abstract: Data suggest that both cancer history and psychosocial stress may be associated with reductions in natural killer cell activity (NKA). Therefore, we tested whether individual differences in cancer history, chronic/perceived stress, and their interactions would be associated with decreased levels of NKA. We tested these hypotheses in 80 spouse caregivers of victims of Alzheimer's Disease (AD) (persons known to report high levels of psychosocial stress) and in 85 age- and sex-matched spouses of non-demented cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 72 publications
2
40
0
Order By: Relevance
“…For example, the work of Vitaliano (4) has shown that caregivers who report higher levels of anger/ hostility have significantly higher levels of glucose, as compared with noncaregivers and caregivers with low levels of anger/hostility. Similarly, the role of caregiving has been shown to interact significantly with existing co-morbidities to predict the following health outcomes: metabolic syndrome (5), natural killer cell activity (6), and blood pressure reactivity (7). On the basis of these findings the current research was undertaken to test the hypothesis that negative neighborhood characteristics would increase the impact of caregiving on biological indicators of physical health.…”
Section: Introductionmentioning
confidence: 96%
“…For example, the work of Vitaliano (4) has shown that caregivers who report higher levels of anger/ hostility have significantly higher levels of glucose, as compared with noncaregivers and caregivers with low levels of anger/hostility. Similarly, the role of caregiving has been shown to interact significantly with existing co-morbidities to predict the following health outcomes: metabolic syndrome (5), natural killer cell activity (6), and blood pressure reactivity (7). On the basis of these findings the current research was undertaken to test the hypothesis that negative neighborhood characteristics would increase the impact of caregiving on biological indicators of physical health.…”
Section: Introductionmentioning
confidence: 96%
“…Sleep is a homeostatic process, an active and periodic biological state that is crucial to physical and mental health and modulated by specific neurotransmitters [4]. It is a common belief that SD increases susceptibility to many diseases [5][6][7], including cardiovascular disease [8][9][10]. Historically, SD was used as a scientific tool to understand the function of sleep.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the effects of chronic stress on immunity have been studied by comparing caregivers who provide care to sick or disabled relatives with broadly matched controls (1)(2)(3)(4)(5)(6) and the antibody response to vaccination is regarded as a useful model for the studying the effects of stress in this context (7)(8)(9). Older spousal caregivers of dementia patients have been found to show a relatively poor antibody response to both influenza and pneumococcal vaccinations (5,10,11), implying a reduced capacity to fight viral and bacterial infections.…”
Section: Introductionmentioning
confidence: 99%